2012
DOI: 10.1002/eat.22047
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic alliance in two treatments for adolescent anorexia nervosa

Abstract: Objective The aim of this study was to examine the relationship between therapeutic alliance and treatment outcome (remission status) in Family-Based Treatment (FBT) and Adolescent Focused Therapy (AFT) for adolescents with Anorexia Nervosa (AN). Method Independent observers rated audiotapes of early therapy sessions using the Working Alliance Inventory-Observer Version (WAI-o). Outcome was defined using established cut-points for full and partial remission. To control for effects of early symptom improvemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 15 publications
(26 reference statements)
0
35
0
Order By: Relevance
“…Interestingly, Forsberg and colleagues (2013) report that observer-rated alliance differentially predicts full and partial remission for adolescents in treatment for anorexia nervosa (Forsberg et al, 2013). Specifically, they found that observer-rated alliance positively predicts partial remission status (i.e., greater than the 85th percentile for mean body weight for age, height, and gender), but not full remission status (i.e., greater the 95th percentile) at the end of treatment, regardless of whether the adolescent received family based treatment or adolescent-focused therapy.…”
Section: Anorexia Nervosamentioning
confidence: 97%
See 1 more Smart Citation
“…Interestingly, Forsberg and colleagues (2013) report that observer-rated alliance differentially predicts full and partial remission for adolescents in treatment for anorexia nervosa (Forsberg et al, 2013). Specifically, they found that observer-rated alliance positively predicts partial remission status (i.e., greater than the 85th percentile for mean body weight for age, height, and gender), but not full remission status (i.e., greater the 95th percentile) at the end of treatment, regardless of whether the adolescent received family based treatment or adolescent-focused therapy.…”
Section: Anorexia Nervosamentioning
confidence: 97%
“…Five studies have investigated the relationship between therapeutic alliance and outcome in the context of adolescent treatment for anorexia nervosa (Bourion-Bedes et al, 2013;Ellison et al, 2012;Forsberg et al, 2013;Isserlin & Couturier, 2012;Pereira, Lock, & Oggins, 2006). Several of these studies suggest that parent and adolescent ratings of alliance are differentially associated with outcome.…”
Section: Anorexia Nervosamentioning
confidence: 97%
“…Earlier studies also show that parents often feel a stronger alliance with caregivers than the adolescents in treatment do. This had an impact on treatment progress, as patients did not feel secure and felt less positive toward change (Forsberg et al 2013; Halvorsen and Heyerdahl 2007; Isserlin and Couturier 2012). However, parents’ alliances with caregivers are important for their roles as parents and their further support of their children after discharge (Honey et al 2007; Isserlin and Couturier 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, although the authors found that it was possible to achieve a strong parental alliance in FT-AN, no association between parental alliance and full remission at the end of the treatment was found. Unfortunately, the authors do not report whether there was a relationship between parental alliance and a more lenient definition of www.co-psychiatry.com weight outcome (> 85% EBW), which, in an earlier paper from the same study [32], was shown to be predicted by the adolescent alliance ratings and was also found to be predicted by family alliance measures in another study [33]. Forsberg et al [31 & ] suggest several important areas for further research, including studies of alliances between family members, exploration of 'shared sense of purpose' in the patient/parents/therapist alliances and a focus on pinpointing the relationships and dynamics between symptom change and alliance early on in the treatment.…”
Section: Therapeutic Alliancementioning
confidence: 83%